AN ANALYSIS MULTIMODAL OF HUMANITARIAN ISSUES POSTERS - Mulyadi, Ari; Sudana, Dadang (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
Revealing humanity issues through posters is a strategy to address conflicts. Therefore, campaign posters should attract the readers to concern about these issues. The unlimited multimodal texts provide chances to be semantically analyzed. This study focuses on social semiotics with a multimodal perspective in campaign posters that contain humanity issues. This study aims to identify the use of campaign posters in spreading principles of humanity and to reduce the prolonged humanitarian crisis in the world. The study applied reading images theory proposed by Kress & Leeuwen (2006), systemic functional linguistics proposed by Halliday (2004), the connotation of names and terms of address proposed by Keith Allan (2001), social semiotics proposed by Bezemer and Kress (2008), and observed the relation between verbal-visual texts through logico-semantic proposed by Martinec and Salway (2005). The study showed that the campaign posters can be considered as a part of efforts to improve the awareness of freedom, equality, and values comprehensively through multimodal.